Managing financial integration and capital mobility: Policy lessons from the past two decades - Joshua Aizenman; Brian Pinto (University of California, Economics Department, 2011)
The accumulated experience of emerging markets over the last two decades has laid bare the tenuous links between external financial integration and faster growth on the one hand and the proclivity of such integration to fuel costly crises on the other. These crises have not gone without learning. During the 1990s and 2000s, emerging markets converged to the middle ground of the policy space defined by the macroeconomic trilemma, with growing financial integration, controlled exchange rate flexibility and proactive monetary policy. The OECD countries moved much faster towards financial integration, embracing financial liberalization, opting for a common currency in Europe, and for flexible exchange rates in other OECD countries. Following their crises of 1997-2001, emerging markets added financial stability as a goal, self-insured by building up international reserves and adopted a public finance approach to financial integration. The global crisis of 2008-09, which originated in the financial sector of advanced economies, meant that the OECD overshot the optimal degree of financial deregulation while the remarkable resilience of the emerging markets validated their public finance approach to financial integration. The story is not over: with capital flowing in droves to emerging markets once again, history could repeat itself without dynamic measures to manage capital mobility as part of a comprehensive prudential regulation effort.
Keywords: 330; Internationales Finanzsystem; Internationales Währungssystem; Kapitalmarktregulierung; Finanzmarktkrise; Aufstrebende Märkte; OECD-Staaten